Manajemen Guru Pendamping Khusus Di SDN 1.2 Belimbing Raya Kabupaten Tabalong - Sri Hartini Astuti (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
This research based on the reality in the field where in Tabalong Regency itself there is only one elementary school that provides a Special Assistant Teacher for children with special needs in the implementation of inclusive education, so the existence of GPK itself is very difficult to find. The role of GPK in implementation of inclusive education is very important because it is an integral part and supporting pillar in the success of inclusive education. The management of GPK is the same as the management of regular educators but there are some things that need to be considered, given their job is to accompany children with special needs. This research aims to find out how the management of special assistant teachers at SDN 1.2 Belimbing Raya. This is field research with a qualitative approach. The conclusion is that the existence of GPK supports the success of students with special needs not only in improving individual student learning experiences, but also helps create an inclusive and supportive learning environment for all children. Correct management of GPK is very important in ensuring that inclusive education runs effectively and comprehensively. Therefore, appropriate selection and placement, training and professional development, team collaboration, monitoring and evaluation, as well as open and clear communication. Considering the importance of GPK, it would be better for this GPK to have a psychology education background in special needs education.